Trends in Black-White Disparities in Breast and Colorectal Cancer Screening Rates in a Changing Screening Environment: The Peters-Belson Approach Using United States National Health Interview Surveys 2000–2010. Issue 2 (February 2016) - Rao, Sowmya R.; Breen, Nancy; Graubard, Barry I.
Abstract : Objective: Cancer screening utilization rates have changed over time and race disparities have persisted. We apply the Peters-Belson (PB) methodology to assess trends in disparities between blacks and whites in breast and colorectal cancer screening rates in the United States from 2000 to 2010. During this time period, the screening environment has changed for these screening modalities. Methods: Cancer screening data collected in Cancer Control Supplements to the US National Health Interview Survey during 2000, 2003, 2005, 2008, and 2010 were used to estimate disparities between blacks and whites. Using the PB method, logistic regression models with selected covariates were fit to the white sample for each year, sex, and type of screening. The unexplained part of the observed disparity was estimated by the average difference between the expected (from the models) and the observed rates for blacks. Weighted least squares linear regression was used to analyze the trend in unexplained disparities. Results: The black rates were generally lower than white rates for both screening tests. Observed mammogram rates for women ages 50–74 years declined slightly for whites with little trend for blacks. There was no statistical trend in the unexplained disparity. Colorectal cancer screening rates among men and women ages 50–75 years increased for both races. The unexplained disparity decreased over time for women (2.98 to −2.00; P =0.03) and nonsignificantly increased for men (5.1 to 8.6; P =0.62). Higher education, health insurance, and a usual source of care were significantly predictive of cancer screening between 2000 and 2010. Conclusions: Over the period we studied, screening rates in the United States increased for colorectal cancer but were stable or declining slightly for mammography. Our PB analysis provides evidence that the unexplained disparity in colorectal screening among women decreased between 2000 and 2010. It is important to continue to study trends over time to evaluate whether the Affordable Care Act will reduce the unexplained disparity for cancer screening in subgroups of the population by increasing insurance coverage and usual source of care among all Americans. Abstract : Supplemental Digital Content is available in the text.